2016
DOI: 10.1007/s11270-016-2926-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of Target Algae by Using Copper-Based Algaecides: Effects of Algal Cell Density and Sensitivity to Copper

Abstract: Public concerns regarding the use of copperbased algaecide for controlling problematic algae may arise due to the risks it creates to non-target algae. To examine this concern, a series of comparative algal toxicity experiments were conducted to study effects of prokaryotic and eukaryotic algal cell densities on their responses to exposures of copper sulfate and copper-ethanolamine (Cu-EA). Microcystis aeruginosa and Pseudokirchneriella subcapitata were cultured separately in BG 11 medium to three initial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The species-dependent variation in algal sensitivity to copper was also recently reported by Tsai35. The 96-h-EC 50 value in Microcystis species to Cu 2+ was in the order of M. flos-aquae  >  M. viridis  >  M. aeruginosa > M. wesenbergii and ranged from 0.09 to 0.49 mg L −1 .…”
Section: Discussionsupporting
confidence: 77%
“…The species-dependent variation in algal sensitivity to copper was also recently reported by Tsai35. The 96-h-EC 50 value in Microcystis species to Cu 2+ was in the order of M. flos-aquae  >  M. viridis  >  M. aeruginosa > M. wesenbergii and ranged from 0.09 to 0.49 mg L −1 .…”
Section: Discussionsupporting
confidence: 77%
“…In the high‐density algal treatments, similar sorption occurred in the 2 formulations, although it was significantly decreased from the low‐density treatments. This may suggest greater interaction of some binding sites with either formulation though overall decreased sorption per cell because of a lower copper to cell ratio (Franklin et al ; Tsai ). Captain was significantly more potent to algae at higher‐density exposures than copper sulfate, suggesting that sorption alone did not correlate with toxicity and that chelated copper may introduce more internal copper to the cells, thereby imparting more toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium had similar effects on the toxicity of nickel and cobalt to Aerobacter aerogenes, and it was found that higher levels of magnesium reduced the amounts of these metals bound by the cell [57]. Tsai [58], in a study of chromium and copper sensitivity in K. aerogenes, found both have synergistic and antagonistic effects. Very low concentrations of Cd 2+ or Zn 2+ potentiated the lethal action of Cu 2+ , mixtures of Cu 2+ and CrO 4 2gave an additive response, and mixtures of Cd 2+ with CrO 4 2were antagonistic.…”
Section: -mentioning
confidence: 97%